Family History of Migraine Associated With Posttraumatic Migraine Symptoms Following Sport-Related Concussion. Issue 1 (January 2018) - Sufrinko, Alicia; McAllister-Deitrick, Jamie; Elbin, RJ; Collins, Michael W.; Kontos, Anthony P.
Abstract : Objective: To determine whether family history of migraine increased the likelihood of posttraumatic migraine (PTM) symptom presentation in adolescents following concussion, and examine the influence of family history of migraine and PTM on postinjury outcomes. Setting: Outpatient concussion clinic. Participants: A total of 153 patients with concussion (103 males and 50 females) aged 15.72 ± 1.48 years (range 12–18 years). Design: Cross-sectional, observational study of patients presenting for initial evaluation 4.72 ± 3.05 days (range 1–14) postinjury. Main Measures: Computerized neurocognitive testing, symptom report, and vestibular/oculomotor screening. Results: Patients with a family history of migraine were 2.6 times (odds ratio = 2.60, confidence interval = 1.35–5.02, P = .003) more likely to present with PTM compared with patients without a family history. Results of multivariate analyses of covariance, controlling for concussion history, revealed significant main effects for PTM on (1) Immediate Post-Concussion Assessment and Cognitive Testing (ImPACT)/Post-Concussion Symptom Scale (PCSS) ( F = 15.43, P <.001) and (2) Vestibular/Ocular Motor Screening (VOMS) ( F = 8.52, P < .001). There was no main effect for family history of migraine on ImPACT/PCSS ( P = .22) and VOMS ( P = .83) or interaction between family history of migraine and PTM on ImPACT/PCSS ( P = .84) and VOMS ( P = .52). Conclusion: Family history of migraine is associated with PTM symptoms following sport-related concussion, suggesting a genetic predisposition for migraine may serve as a catalyst or trigger for onset of PTM. However, only presence of PTM, rather than family history of migraine, was related to worse neurocognitive and vestibular/oculomotor outcomes.